2020
DOI: 10.1037/pspi0000238
|View full text |Cite
|
Sign up to set email alerts
|

Life lacks meaning without acceptance: Ostracism triggers suicidal thoughts.

Abstract: Eleven studies (N = 2,254; 2 preregistered) examined whether ostracism would trigger suicidal thoughts and whether perceived meaning in life would account for this effect. The feeling of ostracism was induced via recalling a past experience (Studies 1a, 1c, 2c, and 3b), imagining a future experience (Studies 1d, 1e, and 2b), engaging in an online real-time interaction (Studies 1b and 2d), or receiving bogus personality feedback (Study 3a). Across all 11 studies, ostracism increased suicidal thoughts. Study 1a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 131 publications
1
34
0
Order By: Relevance
“…In this intermediary path, perceived social support positively predicted meaning in life, while meaning in life negatively predicted hopelessness. This result was similar to those of past studies, and indicated that establishing interpersonal networks helps residents feel a societal connection, thus creating a sense of meaning and a decrease in depression or suicidal thoughts ( Chen et al, 2020 ; Deci & Ryan, 1985 ). The thriving through relationships model and self-determination model state that perceived social support increases residents' sense of belonging and self-worth, which are important for finding purpose and meaning in their lives and purpose for the future in unsafe environments ( Feeney & Collins, 2015 ; Haslam et al, 2015 ; Stillman et al, 2009 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this intermediary path, perceived social support positively predicted meaning in life, while meaning in life negatively predicted hopelessness. This result was similar to those of past studies, and indicated that establishing interpersonal networks helps residents feel a societal connection, thus creating a sense of meaning and a decrease in depression or suicidal thoughts ( Chen et al, 2020 ; Deci & Ryan, 1985 ). The thriving through relationships model and self-determination model state that perceived social support increases residents' sense of belonging and self-worth, which are important for finding purpose and meaning in their lives and purpose for the future in unsafe environments ( Feeney & Collins, 2015 ; Haslam et al, 2015 ; Stillman et al, 2009 ).…”
Section: Discussionsupporting
confidence: 90%
“…Although no previous studies have directly tested the mediating role of meaning in life between perceived social support and hopelessness, there is evidence indicating that without social connection, people would lack life meaning and harbor suicidal thoughts ( Chen et al, 2020 ). Specifically, the thriving through relationships model proposes that perceived social support not only changes the way people make inferences about stress, but it can also activate recipients' participation in life, broadening and constructing individual resources, and help individuals find purpose and meaning in life ( Feeney & Collins, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Howell and Shepperd (2017) found that selfaffirmation decreased the avoidance of health risk information engendered by ostracism. Chen et al (2020) found that self-affirmation reduced suicidal thoughts triggered by ostracism. On the basis of these theories and findings, it is reasonable to suggest that self-affirmation buffers the negative effect of ostracism on self-continuity.…”
Section: Self-affirmation Buffers the Negative Effect Of Ostracism On Self-continuitymentioning
confidence: 99%
“…Besides the direct link between ostracism and self-continuity, various theories assume that ostracism has a negative effect on self-esteem (Leary & Baumeister, 2000;Leary & Downs, 1995;Smart Richman & Leary, 2009;Williams, 1997Williams, , 2009. Indeed, a wide range of empirical research has provided converging support that ostracism disrupts both the need for and the state of self-esteem (e.g., Chen et al, 2020;Ferris et al, 2015;Leary et al, 2003;Li et al, 2019). As important as the aspect of self-concept, selfesteem affects a wide range of constructs.…”
Section: Ostracism Disrupts Self-continuitymentioning
confidence: 99%
See 1 more Smart Citation